2012
DOI: 10.1021/jp302472e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Added Silica Nanoparticles on Hectorite Gels

Abstract: We present a study on the macroscopic, microscopic, and rheological behavior of mixtures of natural hectorite clay and different types of anionic Ludox silica spheres. Adding silica spheres to the weak hectorite gels leads the collapse of the suspensions, while the strong gels remain space-filling, though their storage modulus and the yield stress values diminish. We discuss what kind of structural rearrangements are possibly responsible for the macroscopic and rheological changes in the clay/silica mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…This may be due to enhancement of double‐layer interactions between smectite particles. Several studies have investigated the effect of silica nanoparticles (amorphous silica, ~20 nm diameter) on the rheological behavior of smectite suspensions (Hilhorst et al, ; Kleshchanok et al, ; Landman et al, ). These works found that small quantities of silica nanoparticles can significantly modify the transitional behavior of the liquid crystal phases in smectite suspensions.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to enhancement of double‐layer interactions between smectite particles. Several studies have investigated the effect of silica nanoparticles (amorphous silica, ~20 nm diameter) on the rheological behavior of smectite suspensions (Hilhorst et al, ; Kleshchanok et al, ; Landman et al, ). These works found that small quantities of silica nanoparticles can significantly modify the transitional behavior of the liquid crystal phases in smectite suspensions.…”
Section: Discussionmentioning
confidence: 99%
“…These have been investigated ever since Zocher and Langmuir reported liquid crystalline phases in dispersions of vanadium pentoxide ribbons [1] and hectorite clay platelets [2]. However Langmuir's work has so far proven impossible to reproduce [3][4][5]. Onsager matched theory to work done on the rod shaped tobacco mosaic virus (TMV) and suggested that the level of anisotropy in the particles is the reason for the phase separation, with the loss of orientational entropy in the nematic phase compensated for by the increase in translational entropy [6].…”
Section: Introductionmentioning
confidence: 99%
“…where negatively charged clay particles are mixed with negatively charged nanoparticles. In a series of papers, Lekkerkerker and co-workers 89,110,147,148 looked at the effect of anionic silica nanoparticles on hectorite, montmorillonite and beidellite. At low clay concentrations the silica addition led in general to weaker gels compared to the pure clay system and to incipient phase separation, although the specic manifestation of this differed according to the clay.…”
mentioning
confidence: 99%